2010
DOI: 10.1007/s12892-010-0068-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of new maize hybrids based on SSR markers as compared with other molecular and biochemical markers

Abstract: Genetic diversity of four new yellow single crosses, five new yellow three-way crosses, and five yellow inbred lines of maize (Zea mays L.) was studied using different molecular (SSR, ISSR, and RAPD) and biochemical markers (seed storage protein content). All markers were able to clearly separate the inbred lines in one cluster from the different types of hybrids. The correlation among the different types of molecular markers was moderately high according to the Mantel's test (e.g. 0.67 between SSR and ISSR, 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…However, it was lower than those reported by Nyaligwa et al (2015) and Pandit et al (2016). The high level of polymorphism observed in this study for both marker types (RAPD and SSR) is consistent with the previous studied of Senior et al (1998), Souza et al (2008) and Abdellatif & Khidr (2010) which reported that the polymorphism levels for different types of molecular markers were high in maize. Souza et al (2008) found that SSR markers obtained higher levels of polymorphism than RAPD markers in maize.…”
Section: Levels Of Polymorphismsupporting
confidence: 93%
“…However, it was lower than those reported by Nyaligwa et al (2015) and Pandit et al (2016). The high level of polymorphism observed in this study for both marker types (RAPD and SSR) is consistent with the previous studied of Senior et al (1998), Souza et al (2008) and Abdellatif & Khidr (2010) which reported that the polymorphism levels for different types of molecular markers were high in maize. Souza et al (2008) found that SSR markers obtained higher levels of polymorphism than RAPD markers in maize.…”
Section: Levels Of Polymorphismsupporting
confidence: 93%
“…SSRs can be filtered by the number of nucleotides in the motif and by their length, revealing that reproductive transcriptome has hexanucleotide motifs in 501 TTs, tetranucleotide motifs in 575 TTs, and that 493 SSRs have more than 20 nt in length. SSRs have direct applications as molecular markers since they are easily converted in primers ( Guerrero et al, 2010 ) that provide co-dominant and stable results ( Abdellatif and Khidr, 2010 ) that overcome the limitations of other types of molecular markers ( Garcia et al, 2004 ). Moreover, ORF-based SSRs are more advantageous since they will reduce the mapping efforts required for the development of high-density maps and association studies, and will facilitate comparative genomics.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular analysis was executed using gel documentation system for the dendogram and estimation of similarity index (D-value) of each primer among the studied mutelid species. RAPD-PCR amplification products took the score 1/0 for presence/absence of homologous bands [14] and analyses were accomplished using the NTSYSpc 2.2 software [15] . For RAPD markers, similarity coefficient matrix was calculated using Jaccard similarity algorithm [16] .…”
Section: Molecular Data Analysismentioning
confidence: 99%